Kondo-attractive-Hubbard model for the ordering of local magnetic moments in superconductors - Bertussi, Pedro R.; Malvezzi, André L. [UNESP]; Paiva, Thereza; Dos Santos, Raimundo R. (American Physical Society (APS), 2009)
We consider local magnetic moments coupled to conduction electrons with on-site attraction in order to discuss the interplay between pairing and magnetic order. We probe the ground-state properties of this model on a one-dimensional lattice through pair binding energies and several correlation functions calculated by means of density-matrix renormalization group. A phase diagram is obtained (for fixed electron density 1/3) from which we infer that coexistence between magnetic order and superconductivity is robust at the expense of a continuous distortion of the magnetic arrangement of the local moments as evidenced by a strong dependence of the characteristic wave vector k on the coupling constants. This allows us to understand some trends of the coexistence, such as the influence of the rare earth on k, as observed experimentally in the borocarbides. © 2009 The American Physical Society.